4,4’-Bipyridinium 1,1,2,3,3-pentacyanopropenide — new convenient building block for the crystal engineering - Poltorak, D.V.; Gutov, A.V.; Rusanov, E.B.; Chernega, A.N. (Украинский химический журнал, 2009)
The successful combination of the known tectones — 4,4’-bipyridinium cation and 1,1,2,3,3-pentacyanopropenide anion — demonstrate a promising for study and modifications crystal structure with four strong intermolecular interactions of different types and directions (three orthogonal), namely: resonance-stabilized H-bonds, aromatic π-stacking, π-stacking of acyclic systems, and Coulomb attraction amplified by multiple C–H...N contacts; furthermore, there are four groups of chemically equivalent H-bonds directed along the same axis and two different anion geometries in seemingly equal environments. Crystal data: a=9.767(4), b=13.465(8), c=14.274(7) Å, α=97.67(4)⁰, β=107.89(3)⁰, γ=108.19(4)⁰, V=1642(2) Å³, space group P 1 (N 2). Удачная комбинация двух известных тектонов — катиона 4,4’-бипиридиния и аниона 1,1,2,3,3-пентацианопропиленида — демонстрирует многообещающую для исследований и модификаций кристаллическую структуру с четырьмя сильными межмолекулярными взаємодействиями различных типов и направленности (три из которых взаимно ортогональны), а именно: резонансно-стабилизированные водородные связи, ароматический π-стекинг, π-стекинг ациклических систем и кулоновское притяжение, усиленное C–H...N-контактами. Более того, в кристалле четыре группы химически эквивалентных водородных связей направлены вдоль одной оси; два аниона имеют разные геометрические параметры в приблизительно одинаковом окружении. Основные кристаллографические параметры: a=9.767(4), b=13.465(8), c=14.274(7) Å, α=97.67(4)⁰, β==107.89(3)⁰ γ=108.19(4)⁰, V=1642(2) Å³, пространственная группа P 1 (N 2). Вдале поєднання двох відомих тектонів — катіону 4,4’-біпіридинію та аніону 1,1,2,3,3-пентаціанпропіленіду — демонструє багатообіцяючу для досліджень та модифікацій кристалічну структуру з чотирма сильними міжмолекулярними взаємодіями різних типів та направленості (три з яких ортогональні), а саме: резонансно-стабілізовані водневі зв’язки, ароматичний π-стекінг, π-стекінг ациклічних систем та кулонівське притягання, посилене C–H...N-контактами. Більше того, у кристалічному стані чотири групи хімічно еквівалентних водневих зв’язків направлені вздовж однієї осі; два аніони мають різні геометричні параметри у приблизно однаковому оточенні. Основні кристалографічні параметри: a=9.767(4), b=13.465(8), c=14.274(7) Å, α=97.67(4)⁰, β=107.89(3)⁰, γ=108.19(4)⁰, V=1642(2) Å³, просторова група P 1 (N 2).